2018
DOI: 10.1002/cepa.661
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction Hazards from “Inherited Vulnerabilities”

Abstract: This paper discusses two forms of soil liquefaction that are particularly damaging for engineering structures and communities: liquefaction of reclaimed land and urban liquefaction. Case histories from recent New Zealand earthquakes are used to illustrate characteristics of liquefaction manifestation and associated damage to land and structures. Liquefaction of gravelly fills at Wellington port and influence of finer sand‐silt fractions on the liquefaction performance of well‐graded gravelly reclamations are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Recent investi gations have highlighted that earthquakes can trigger shear strength loss in a broad range of types of saturated soils, from sand to low plasticity clays (BRAY et al, 2004, CHU et al, 2004, although earthquakeinduced ground failure is observed less frequently in clays than in sands. CUBRINOVSKI et al (2018) reported liquefaction in well graded gravel with at least 30% of sands and silts during the Kaikoura (New Zealand) earthquake (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent investi gations have highlighted that earthquakes can trigger shear strength loss in a broad range of types of saturated soils, from sand to low plasticity clays (BRAY et al, 2004, CHU et al, 2004, although earthquakeinduced ground failure is observed less frequently in clays than in sands. CUBRINOVSKI et al (2018) reported liquefaction in well graded gravel with at least 30% of sands and silts during the Kaikoura (New Zealand) earthquake (2016).…”
Section: Introductionmentioning
confidence: 99%